PENGUNGKAPAN ENVIROMENTAL, SOCIAL, DAN GOVERNANCE (ESG) TERHADAP REAKSI PASAR (Studi Empiris pada Indeks Kompas 100 yang mengungkapkan ESG Score dan Terdaftar di BEI Tahun 2019-2021) (Diponegoro Journal of Accounting, 2023)
This study examines the Environmental, social, governance relationship on market reaction. This study has a dependent variabel, namely market reaction with independent variabels Environmental Disclosure, social Disclosure, governance Disclosure. Also Return on Asessets and Return on Equity as control variabels. This study uses secondary data derived from the financial statements of indeks kompas 100 sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The research samping was carried out using purposive sampling method. 127 samples were obtained for 3 consecutive years. This study uses multiple linear regression alaysis to test the hypothesis. The finding from this study proves that Environmental Disclosure have a significant positif to market reaction. While social Disclosure and governanace Disclosure has no significant to market reaction.